Acomparison Study between Barley and Concentrate feeding on the growth and digestibility of Karadi male Lambs - Sadq, Sarwar M. (Sulaimani Journal for Pure and Applied Sciences, 2018)
Twenty six Karadi male lambs were used in this experiment with an average live body weight of 28.7± 0.553 kg. Lambs were 5 months old and assign randomly to two feeding groups of thirteen lambs each. Lambs in the first group were fed a whole barley grain based diet and the second group were fed a concentrate pellets. Both groups received ad-libitum of chopped barley straw. All lambs were received an equal daily allowance of concentrate pellet or barley grain (3 % of their body weights). Lambs were fed their rations for 9 weeks. At the 8th week of the feeding period, the apparent digestibility trial was conducted on four ram lambs of each group, where the total feed intake and feces was recorded. The result showed that lambs fed concentrate pellet significantly (P<0.05) had better total gain, average daily gain, daily feed intake and feed conversion ratio as compared with the lambs fed whole barley grain. Average daily nutrient intake and in vivo apparent digestibility of DM, OM, CP, EE, CF and NFE were significantly (P<0.05) higher in lambs fed concentrate pellet as compared to the barley fed group. In conclusion, the lambs fed concentrate pellet diet had better performance, digestibility of nutrients and more economical as compare to lambs fed barley grain.
Keywords: Barley; concentrate pellet; digestibility; Karadi lambs performance